Edukasi Zero Waste berbasis teknologi informasi - Wirasasmita, Rasyid Hardi; Arianti, Baiq Desi Dwi; Uska, Muhammad Zamroni; Kholisho, Yosi Nur; Wardi, Zoatul (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2020)
This Community Service program aims to socialize the Zero Waste (ZW) environmental program and to train the community to manage waste (used goods) into goods that can be recycled using an Android-based application. The methods used are lectured and demonstrations (hands-on training). For education on the Zero Waste environmental programÂ through the Zero Waste application, while for training through demonstrations or direct training (practice). The location for implementing this community service is in Lengkok Lendang hamlet, Tembeng Putik village, East Lombok regency, Nusa Tenggara Barat (NTB) province. So far, at Tembeng Putik there has never been any training on Waste Management and the Zero Waste environment program so that public knowledge and awareness about environmental health are still low. The results obtained are the formation of this knowledge about the importance of the Zero Waste environment, and the community can make or manage waste into more useful finished goods.